ANÁLISE DA OCORRÊNCIA DE INFECÇÕES HOSPITALARES EM PACIENTES SUBMETIDOS À CIRURGIA CARDÍACA - Andrade, Érica Vieira de (2012)
Hospital infections are a worldwide public health problem and its occurrence after cardiac surgery represents a serious complication that always leads to evil consequences. This research aimed to analyze the occurrence of nosocomial infections in patients undergoing cardiac surgery in a teaching hospital in Minas Gerais in the period from July 2005 to July 2010. It is a retrospective, longitudinal study with a quantitative approach, conducted with 460 patients. This study was approved by the Ethics Committee in Research of UFTM in opinion No. 1611. Data were collected from reporting of hospital infection and patients' records, using an instrument consisting of demographic data, clinical and related to the perioperative period. For data analysis we used SPSS software. Qualitative variables were analyzed using descriptive statistics and were used for the quantitative descriptive measures of centrality and dispersion. To identify risk factors associated with nosocomial infection and to investigate the relationship between infection and occurrence of death was performed bivariate analysis and then multivariate logistic regression analysis (α=0.05). To investigate the relationship between the occurrence of infection and length of stay postoperative used the Student t test (α=0.05). The incidence of patients with hospital infection was 24.3% and infectious sites identified in the study population were respiratory tract, surgical site, urinary tract, bloodstream, pressure ulcers, peritonitis, endocarditis and otitis. The respiratory tract infection had a higher incidence (20.6%) when compared to other sites. Of the patients with respiratory tract infection the most common microorganism (42.8%) was Pseudomonas aeruginosa. Of the patients with surgical site infection, Staphylococcus aureus was the prevalent microorganism (40.0%). Klebsiella pneumoniae was the most frequent pathogen in patients with urinary tract infection (50.0%) and bloodstream (66.7%). Of infection in patients with pressure ulcers, were isolated Enterobacter cloacae (50.0%), Klebsiella pneumoniae (50.0%), Morganella morganii (50.0%) and Escherichia coli (50.0%). Of the antibiotics used postoperatively, cefepime was used by the majority (79.0%) of the patients. It was found that intubation time (p=0.005), duration of central venous catheter (p<0.001) and length of stay of indwelling urinary catheter (p<0.001) were independent predictors of postoperative hospital infection in this population. The occurrence of nosocomial infection (p<0.001) and postoperative complications (p=0.001) were independent predictors for the occurrence of death after heart surgery. The death rate among patients who developed hospital infection was 32.1% and among patients without infection was 4.6%. The mean postoperative hospital stay was significantly (p<0.001) higher for patients with nosocomial infection (23.5 days) than for patients without infection (8.2 days). It is hoped that this research will contribute in developing and implementing protocols for the prevention and control of nosocomial infections, in addition to supporting the development of other studies related to this subject.